2002
DOI: 10.2527/2002.8041005x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects on fatty acid composition of carcass fat of Japanese Black Wagyu steers

Abstract: Two hundred ninety-three Japanese Black Wagyu steers derived from 34 sires were used to investigate genetic effects on the fatty acid composition of carcass fat. All steers were fed identical diets for 365 d and slaughtered at similar ages. If the percentage of genetic contribution of sire A, B, or C was not lower than 25%, steers were classified into groups A, B, and C, respectively. Fatty acid compositions differed depending on deposit sites. Mean percentage of monounsaturated fatty acids (MUFA) tended to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
71
2
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 24 publications
13
71
2
1
Order By: Relevance
“…The BMS value determined in this study was found to be higher than the value (4.0) reported by Oka et al (2002), using Japanese Black steers fattened in a similar fattening test. However, the present value is similar to the value of 7.1, which was reported by Inoue et al (2008), using steers and heifers.…”
Section: Phenotypic Measurementscontrasting
confidence: 90%
See 2 more Smart Citations
“…The BMS value determined in this study was found to be higher than the value (4.0) reported by Oka et al (2002), using Japanese Black steers fattened in a similar fattening test. However, the present value is similar to the value of 7.1, which was reported by Inoue et al (2008), using steers and heifers.…”
Section: Phenotypic Measurementscontrasting
confidence: 90%
“…However, the present value is similar to the value of 7.1, which was reported by Inoue et al (2008), using steers and heifers. In addition, the average values for fatty acid composition and MUFA were found to be similar to those of intramuscular adipose tissue of M. longissimus reported by Oka et al (2002), although the percentages of saturated fatty acids in their report were slightly higher and those of unsaturated fatty acids and MUFA were slightly lower than the percentages determined in this study.…”
Section: Phenotypic Measurementssupporting
confidence: 85%
See 1 more Smart Citation
“…Quantity is the outcome of muscle fibre hyperplasia and hypertrophy. Hyperplastic growth in utero is primarily dependent on myocyte proliferation and differentiation (Oka et al, 2002). Post-natal growth is mainly the result of hypertrophy or enlargement of existing and replaced muscle fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Activities of enzymes related to energy metabolism in leukocytes are considered to reflect the metabolic states in animal tissues [2,3,24]. On the other hand, plasma glucose and insulin concentrations are different between dairy and beef cattle [12,15,20,22]. It has been reported that Japanese Black heifers have higher plasma insulin level at 18 mo of age than at or before 12 mo of age, whilst Holstein heifers have very similar values at all stages [19].…”
mentioning
confidence: 99%